2011
DOI: 10.1007/s11882-011-0221-8
|View full text |Cite
|
Sign up to set email alerts
|

Should Newborns be Screened for Immunodeficiency? Lessons Learned from Infants with Recurrent Otitis Media

Abstract: Recurrent otitis media in children is considered one of the warning signs of primary immunodeficiencies (PIDs), particularly antibody deficiencies. Infants who have the most serious and potentially lethal form of PID, severe combined immunodeficiency (SCID), sometimes present with recurrent otitis media. Most of the time, because of the severity of the immune defect, they develop more serious and systemic infections. SCID is distinct among the PIDs and considered a pediatric emergency. Diagnosing SCID during t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…Studies analyzing the middle ear of allergic rhinitis and asthma patients concluded that both the middle ear and nose mucosa share the same immunological features, supporting the unified airway concept [ 25 ]. Limited information is available regarding the role of other less common immunological disorders, but some findings regarding middle ear and nasal infections in primary and acquired immuno-deficiencies suggest that increased attention should be paid by the scientific community in future studies [ 30 , 31 ]. It was already demonstrated that COM and CRS shared the same pathogens from cultures of the middle ear and sinuses [ 32 ] and that biofilm, a cause of chronic mucosal infection, can involve both the middle ear and paranasal mucosa [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies analyzing the middle ear of allergic rhinitis and asthma patients concluded that both the middle ear and nose mucosa share the same immunological features, supporting the unified airway concept [ 25 ]. Limited information is available regarding the role of other less common immunological disorders, but some findings regarding middle ear and nasal infections in primary and acquired immuno-deficiencies suggest that increased attention should be paid by the scientific community in future studies [ 30 , 31 ]. It was already demonstrated that COM and CRS shared the same pathogens from cultures of the middle ear and sinuses [ 32 ] and that biofilm, a cause of chronic mucosal infection, can involve both the middle ear and paranasal mucosa [ 33 ].…”
Section: Discussionmentioning
confidence: 99%